Clinic and Radiographic Evaluation of Cemento-osseous Dysplasia: Case Series - Nuray Bağcı; Özlem Üçok; İlkay Peker (Ankara University, 2022)
Aim: Cemento-osseous dysplasia (COD) is usually asymptomatic and slowly progressive benign fibro-osseous lesion characterized by the replacement of normal bone with fibrous tissue. The aim of this presentation is to evaluate the clinical and radiographical findings of six COD cases that were detected incidentally during radiographic examination. Case Report: Six female patients who four (%66) of them with different dental complaints and two (%33) of them for routine control examination of the previously diagnosed COD with a mean age of 38 applied to our clinic. It was learned that the patients did not have any systemic disorders in their medical anamnesis. There is not any finding on extraoral examination. In intraoral examination, teeth associated with COD lesions were vital as a result of the electric pulp test, and there is no other finding related to the lesion. In the radiography examination, different sizes radiolucent, mixed, and radiopaque lesions were detected in the mandible on control panoramic radiographs. The lesions were examined in detail with cone-beam computed tomography. Local thinning and resorption were observed in the buccal and lingual cortical bone in the relevant region. Histopathological examination revealed that the lesions were definitively diagnosed as SOD in four patients. Based on clinical, radiographic, and histopathological examinations, three (%50) of the lesions were diagnosed as periapical COD and the others (%50) were diagnosed with fluoride COD. All patients were followed up periodically for six months. Conclusion: The findings of this case series showed that all lesions examined were clinically asymptomatic and mixed on radiography. Due to insufficient vascular support of the bone in the COD area, there is a risk of infection and osteomyelitis may occur. Therefore, dentists should be aware of the clinical and radiographic features of COD in clinical practice and follow the patients periodically.